Purple Sunset Pomegranate (Punica granatum ‘PIIPG-1’) - Gary W. Knox (EDIS)
Purple Sunset is a new ornamental cultivar of pomegranate, Punica granatum. Purple Sunset pomegranate is distinguished from fruiting pomegranate by a bushy, compact habit and numerous flowers followed by small, ornamental, purple-black fruit. This 2-page fact sheet was written by Gary W. Knox and published by the UF Department of Environmental Horticulture, June 2014.